A comparison between cannulated and non-cannulated cancellous screws used in the fixation of a simulated femoral neck fracture – a finite element study - Huang, Jun (2018)
Femoral neck fracture frequently occurs in aged groups and has been recognized as a major health issue. Cannulated cancellous screws are commonly used for the fixation. In prior studies, various performances and configurations of screws have been studied with involvement of characteristics of pull-out strength, different load, displacement and stiffness. The aim of this the project is to use finite element method (FEA) to compare the cannulated and non-cannulated cancellous screws used in fixation for femoral neck fracture by modeling. In this study, the three screws, together with a fourth generation composite femur were applied in an inferior triangular fixation on Pauwel’s type-2 vertical femoral neck fracture. It was found that the femur model with cannulated screws experienced a higher von Mises stress as compared with non-cannulated screws at both maximum and specific loading conditions. Thus, the non-cannulated screws perform better on resisting load than cannulated screws.